Pedagogical Mechanisms of Experiential Learning: Kinesthetic Simulations for Facilitating Democratic Character - Ary Purwantiningsih; Ibnu Sulaiman; M. Khanif Yusman; Heni Cahya Ramdani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
Rote-oriented civic education may provide limited opportunities for students to connect abstract democratic principles with practical experience. Although experiential learning is increasingly used in civic education, the pedagogical processes through which kinesthetic simulations encourage critical reflection and democratic learning remain insufficiently explained. This qualitative case study examined how an outdoor collaborative kinesthetic simulation supported democratic learning among secondary school students. Data were collected through participant observation, semi-structured interviews with 18 purposively selected students, and documentation of learning artifacts. The data were analyzed thematically and compared across sources through triangulation. The findings showed that the simulation enabled students to experience cooperation, make collective decisions under time constraints, and participate in inclusive dialogue. These experiences encouraged reflection on power relations, shared responsibility, participation, and civic norms. The simulation therefore functioned as a bridge between physical experience and the interpretation of abstract democratic values rather than merely as a recreational activity. The study illustrates how the stages of experiential learning can be applied within civic education and provides educators with an adaptable instructional strategy for promoting reflective participation and active engagement with democratic principles